A moderated mediation model of perceived effect of fitspiration images on self: the influence of media literacy and BMI - Ahadzadeh, Ashraf Sadat; Wu, Shin Ling *; Ong, Fon Sim; Deng, Ruolan; Lee, Kam-Fong (MDPI, 2022)
The present study investigated the relationship between internal locus of control and the perceived impact of Instagram fitspiration images on the self with media literacy as the mediating role in this relationship. This study also examined the importance of body mass index (BMI) as a moderating factor in the mediated model, where higher BMIs could weaken the relationship between internal locus of control and the perceived effect of fitspiration images mediated through media literacy. A sample of 321 Malaysian university students who were fitspiration viewers filled out a self-report questionnaire assessing internal locus of control, media literacy, perceived effect of fitspiration images on self, body satisfaction and BMI. The data analysis was performed using SPSS PROCESS macro. Results show that internal locus of control is negatively associated with the perceived impact of fitspiration images on self, mediated by media literacy. However, BMI moderates the mediated relationship such that the negative relationship between internal locus of control and the perceived effect of fitspiration images through media literacy does not exert an effect on those with high BMI. These results accentuate the value of incorporating a potential mediator and moderator into the direct relationship between internal locus of control and perceived effect of media ideals on self to provide an enhanced understanding of this process and offer practical insights about the protective role of media literacy and negative effects of high BMI.